Poverty Level Determination Analysis: Case Study of South Sumatra Province - Mirrahma, Aliyah Aisyiyah; Septiani, Msy Aziza; Panorama, Maya (Universitas Alma Ata, 2023)
Poverty is a multidimensional problem related to economic, political, social, cultural, and community participation. This is evidenced by the increasing trend of the number of people living below the poverty line. The main trigger of poverty in Indonesia is the inequality of economic distribution or what is known as economic justice. Whereas all religions prohibit economic monopoly actions that cause injustice and order their people to give charity (zakat) and cooperate evenly. Intending to reduce the poverty rate of the community even though we still often hear of hunger and hardship for some humans. This means that the welfare that is expected and aspired to has not been realized for people's lives. According to BPS 2022 data, South Sumatra is included in the top 10 with high poverty rates. Therefore, this study aims to determine, explain and analyze the factors that affect the Percentage of the Poor Population (PPM) in South Sumatra for the period 2019-2022. This research method uses a panel data regression method with individual unit observations of as many as 17 districts and cities of South Sumatra province in four years from 2019 to 2022. This study uses one response variable, namely PPM, and four explanatory variables, namely the unemployment rate (TPT), average years of schooling (RLS), GRDP per capita, and human development index (HDI). The results of this study show that the fixed effect model with two-way specific effects is the best model of the panel data poverty rate. Variables that have a significant effect are GRDP. RLS. and HDI.